Habitat Variations of Two Commercially Valuable Species Along the Chilean Waters Under Different-Intensity El Niño Events - Feng, Zhiping; Yu, Wei; Zhang, Yang; Li, Yunkai; Chen, Xinjun (Frontiers in Marine Science, 2022)
Synchronous response of the spatial distribution pattern of Dosidicus gigas and Trachurus murphyi habitat along the Chilean waters to multi-intensity El Niño events was examined based on the habitat suitability index models (HSI) inclusive with the key environmental factors of sea surface height anomaly (SSHA), sea surface salinity (SSS), water temperature at 400 m depth (Temp_400 m) for D. gigas, sea surface temperature (SST), mixed layer depth (MLD), Temp_400 m for T. murphyi and Niño 1+2 index. Results showed that all the environmental factors except MLD were significantly correlated with the Niño 1+2 index. Compared with weak (WE) and moderate (ME) El Niño events, the suitable range of SSHA and SSS for D. gigas decreased, resulting in decreased suitable habitat area and increased poor habitat area during strong (SE) El Niño years. In space, the suitable habitat of D. gigas was mainly distributed in the north-central Chile with an east-west strip pattern, it decreased significantly in the northwestern waters off Chile and moved southwestward under SE El Niño events. For T. murphyi, the ME El Niño events yielded contracted suitable range of water temperature and MLD decreased, consequently leading to decreased suitable habitat area and increased poor habitat area of T. murphyi compared to WE and SE El Niño events,. Suitable habitat of T. murphyi was mainly distributed in the 42o-47oS area and varied non-significantly during the WE and SE El Niño events, however, it clearly decreased in the southwest of Chile and shifted northeastward under ME El Niño events. Our results indicated that El Niño events with different intensities strongly affected the habitat pattern of D. gigas and T. murphyi off Chile by changing the regional marine environment.